Preparation of cellulose-graft-polymethacrylic acid nanocapsule encapsulating gallic acid for cosmetic application - Tangsongcharoen, Wichsuda; Punyamoonwongsa, Patchara; Chaiyasat, Amorn; Chaiyasat, Preeyaporn (Journal of Applied Research on Science and Technology (JARST), 2018)
In this research, the preparation of cellulose nanocapsules encapsulating gallic acid (GA), an important component in Bambara groundnut extracts, by water in oil miniemulsion polymerization was studied using carboxymethyl cellulose (CMC) as a shell. Initially, CMC was modified with 3-(trimethoxysilyl)propyl methacrylate (MPS) as a silane coupling agent at a ratio of CMC:MPS of 75:25 (%w/w). The FT-IR results confirmed the successful modification of CMC. The C=C bonds from silane coupling agent were observed in m-CMC spectrum which were further polymerized with methacrylic acid (MAA) monomer to form 3D-network CMC-graft-polymethacrylic acid shell. Various ratios of m-CMC:MAA and stirring rate for monomer droplet preparation were investigated. It was found that the optimum condition was a m-CMC:MAA at 33:67 and 40% amplitude, respectively. The obtained nanocapsules presented high colloidal stability, spherical shape and nano-sized with high loading and encapsulation efficiency at 24 and 73%, respectively.